SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) TREATMENT EVALUATION OF ADULT PATIENTS WITH SLE - Nancy Nancy; Zullies Ikawati (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease characterized by fluctuating disease activity. SLE treatment in Indonesia is still limited on how to control clinical features and complications that may occur, using glucocorticoids, NSAIDS, antimalarial agents, and cytotoxic drugs. The objectives of this study were to identify treatment patterns and the degree of appropriate treatment among SLE patients. A retrospective study was carried out using medical record data of adult patients with SLE diagnoses in the inpatient department of X Public Hospital Yogyakarta during January-December 2011. Appropriate descriptive analysis was used. The results showed that the most used drugs in SLE pharmacologic therapy were topical antiinflammatory agents 56%, glucocorticoid methylprednisolone 47%, cytotoxic mycophenolate mofetil 17%, antimalarial chloroquine 9%, and NSAID diclofenac sodium 6% while the most common treatment pattern was with glucocorticoid as monotherapy (35%). The degree of appropriate indication, patient, drug, and dosage were 100%, 100%, 53%, and 83% respectively.Keywords : Treatment Evaluation, Systemic Lupus Erythematosus (SLE), Hospital